AL MAUN'S THEOLOGY IN A NEUROSCIENCE PERSPECTIVE - Andy Julianto; Suyadi Suyadi (Profetika: Jurnal Studi Islam, 2023)
This research was conducted to reveal the concept of al ma'un theology from a neuroscience perspective. The method used is a qualitative study, using a literature study paradigm, and using content analysis, historiography, and descriptive approaches. The results of the study concluded that. al Ma'un's Theology under the umbrella of Islamic Theology was initiated and developed by KH Ahmad Dahlan. High-level awareness (spirituality) of students KH. Ahmad Dahlan whose name is Sudjak asked about why he had to read Surah Al Ma'un in every routine Fajr recitation meeting and then how did KH's spiritual or intuitive thinking work. Ahmad Dahlan for his students' questions which were studied and pondered deeply to produce Al Maun's Theology.